Identificação de regiões genômicas e genes candidatos associados com qualidade de carne e conteúdo de minerais no músculo em bovinos da raça Nelore - Tizioto, Polyana Cristine (2014)
This thesis is divided into three chapters in order to facilitate the understanding of the experiments that will be presented. The first chapter refers to a concise literature review, which covers the main theoretical themes and justifications regarding the developed experiments presented in the following chapters. The second chapter presents two genome-wide association studies in Nellore cattle, being the first for meat quality traits and the second for the mineral content of the Longissimus dorsi muscle. Considering the importance of beef tenderness for producer, the third chapter deals with the strategy used to identify candidate genes that explain the variation in this trait in Nellore breed. The experimental results suggested that meat quality traits and mineral content of skeletal muscle is at least partially genetically determined. Most quantitative trait loci (QTLs) identified is of small effects, revealing the polygenic background of those traits and the importance of applications that consider variation at the genomic level. However, some major effect QTLs were found for muscle pH , iron, selenium , zinc and calcium content in muscle, which accounted for 4.01 , 6.53 , 3.53 , 2.59 and 2.55% of the additive genetic variance , respectively. Through these studies, we produced an extensive list of candidates genes and metabolic pathways related to economic interest traits in beef cattle, which should contribute to the understanding of the their underlying genetic mechanisms. A genome-wide association approach still not economically feasible for beef producers, therefore candidate genes strategy is interesting because of its major accessibility. KCNJ11, MyoD1 and ASAP1 candidate genes were identified as explaining part of the variation in meat tenderness of Nellore breed. The validation of genomic regions and candidate genes identified in this study and future mapping of causal mutations should contribute to the implementation of marker-assisted selection and for the genomic selection of traits of economic interest in Nellore cattle.